The Comparison of English Learning Achievement between Online Learning with Online Based on Multimedia - Roisatin, Umi Anis; Thamrin, Moh; Setiawan, Ardian Wahyu (Bulletin of Science Education, 2021)
Learning English before and after the Covid-19 pandemic shows a very different process. Face to face on campus in Indonesia has turned into a learning process entitled Learning From Home. The study aims to describe the challenges faced by lecturers and students in implementing online learning of English. The case study was applied in the study by direct observation of online learning that took place at the State Polytechnic of Malang, documentation of learning materials, assignments, and student assessments and presentations. The results showed that the learning outcomes of the experimental group and the control group did not show a significant difference. It shows that multimedia effects are long term. So that it is faster to understand than just online. While the driving factor is the internet budget. The inhibiting factor is the internet network which is difficult to reach by students whose houses are in remote villages, not all areas are easy to reach internet signals. Another obstacle comes from the students themselves, the lack of awareness of the tasks that students have to do. While the advantages of the learning strategy are students can be monitored directly by parents so that parents can find out to what extent their children understand the subject matter and know the learning deficiencies that exist in students. Keywords: Online Learning, Learning Multimedia, Learning in Covid-19 Condition